PELAYANAN LEMBAGA ZAKAT UNTUK MENINGKATKAN KEPUASAN MUZAKKI - Gunawan, Karebet (ZISWAF, 2017)
Zakat is one of the links of a Muslim identity. Zakat not only benefits the recipients, but can provide enormous benefits to those who issue zakat. Zakat institutions basically in providing services must be transparent and can satisfactory to all parties so that it can lead to loyalty of users. Zakat institutions must work how to create the satisfaction of muzakki so that the funds collected more and more. The payment of zakat through one of zakat institutions is a form of tabligh and at the same time gives an example to other parties to implement the teachings of zakat in an organized manner. In addition, zakat institutions should also improve the quality of service so that with good service the zakat institution users will be more loyal. With loyalty it can cause muzakki more tied with zakat institution.